Infrastructure Facilities Information System (SISAPRAS) as a Monitoring of Educational Service Facilities - Verry Riyanto; Sumarna Sumarna; Hafis Nurdin; Ganda Wijaya (Institute of Computer Science (IOCS), 2021)
The availability of supporting devices in the academic services of a university is inseparable from the location and placement and also the need for these devices. The need for operational equipment is a necessity in the running of business process activities at a university, therefore the types of operational devices and facilities provided are a benchmark for a university in providing the best service to the academic community in it. In a tertiary institution, the need for operational equipment plays an important role in carrying out the teaching and learning process, on the other hand, behind-the-scenes operations also play an active role in ensuring the learning and teaching process runs. The need for operational equipment for infrastructure and facilities will increase where if a university has a building or branch with a different location, with this condition new findings will appear, the types of operational goods proposed are not balanced between branches or the number of goods that will be served by each branch is not monitored. Therefore, an infrastructure information system was built to facilitate and monitor each branch of the university in managing the equipment and operational facilities and infrastructure at the branch of the college building.